When are new energy vehicle incentives effective? Empirical evidence from 88 pilot cities in China. (November 2022) - Yao, Xusheng; Ma, Shoufeng; Bai, Yin; Jia, Ning
Highlights: Empirical evidence for NEV market sales responses to incentive policies is provided. Purchase restrictions are effective in cities with poor air quality or large sizes. The policy mix accounts for 16.9–47.6 % variation in NEV sales in distinct contexts. The NEV industry has a tendency to transition from policy-driven to market-driven. The removal of local fiscal subsidy has a significant, negative effect on NEV sales. Abstract: Incentive policies play an essential role in the rapid expansion of new energy vehicles (NEVs). Based on a comprehensive panel dataset, this paper investigates the effectiveness of various demand-side incentives in 88 NEV pilot cities in China. First, to explore where policies work effectively, we segment the pilots into several categories and conduct group regression. The results indicate that purchase restriction policies are effective in cities with poor air quality or large sizes. Use restrictions take effect only in cities with poor traffic infrastructure. Charge subsidies work in cities with good air quality or good traffic infrastructure. Second, to measure the contribution of policies, we conduct Shapley decomposition and reveal that the policy mix accounts for 16.9–47.6 % of the variation in NEV sales in distinct city categories. The empirical results of the decomposition also confirm the tendency of a transition from policy-driven to market-driven in the NEV industry. Third, to further validate the role of purchase subsidies, we consider the policy removal event in 2019 as a quasi-natural experiment and demonstrate that the removal of local purchase subsidy had a significant, negative effect on NEV sales. In light of the above findings, we suggest that policymakers avoid making one-size-fits-all policies and design precise and personalized policies, such as purchase restrictions (charge subsidies) for cities with poor (good) air quality. Moreover, a long-term, dynamic subsidy scheme remains necessary for the current stage.